PERFORMANCE OF DIFFERENT ACIDS FOR ACIDIZING TREATMENT IN SANDSTONE FORMATION (PANGKOR SAND) - MUHAMMAD ASLAM YUSUF BIN MUSA, MUHAMMAD ASLAM YUSUF (Universiti Teknologi Petronas, 2012)
As more technologies to enhance oil production recovery are being developed, well stimulation has been introduced and it acts as one of the important roles to fulfill the demand of world for energy. Well stimulation is a well intervention performed on an oil or gas well to increase production by improving the flow of hydrocarbons from the drainage area into the wellbore. Well stimulation generally uses fluids which create or enlarge the flow channels of formation so that it can overcome low permeability of formation. A most common and one of the most successful well stimulation is matrix acidizing. In matrix acidizing, acids are injected at matrix pressure below formation fracturing pressure. These acids will react to remove mineral phases that restrict the flow in the formation. The permeability of formation will be increased either by removing the pore-plugging materials in the formation or by creating new or enlarged flow paths in the rock depending on the formation and acid types. In the formation, acid-removable damage may be present. The right type of acid or combination of acids must be used to remove the damage. Thus, careful acid choice and treatment design are critical for a successful matrix acidizing. In this project, determination on which combination of acids used are the best in acidizing treatment in term of increasing porosity and permeability to dissolve minerals in sandstone formation is being clarified. Different combinations of acids are used as the first combinations are between formic acid and hydrochloric acid and the second combinations are between hydrochloric acid and fluoboric acid. Apart from that, in each combination of different acids, the most suitable acid formulations are being obtained. The samples that will be used for experimental works in this project are the sands that came from Pangkor Island.